A comprehensive estimate of life cycle greenhouse gas emissions from onshore wind energy in China. (1st March 2022) - Xu, Kang; Chang, Jinfeng; Zhou, Wenji; Li, Shuangcheng; Shi, Zhou; Zhu, Hanwen; Chen, Yaoyao; Guo, Kaiwen
Abstract: Rapid deployment of wind energy plays an important role in China's proposed energy transition to carbon neutrality before 2060. Greenhouse gas (GHG) emissions are, however, unavoidable during the entire life cycle of wind energy from manufacturing to disposal. It is important to estimate these GHG emissions and the emission intensity for programs of energy transition. In this study, simplified LCA models and engineering-based models were developed to provide a comprehensive estimate of the GHG emission intensity from onshore wind energy in China at provincial and national scales. Results showed that in 2019, the GHG emission intensity per unit power generation was 19.88 g CO2 eq/kWh (provincial intensity ranges from 13.59 to 34.50 g CO2 eq/kWh). The results indicated that onshore wind energy in China has an emission intensity more than 98% lower than traditional fossil fuels and the mitigation effect can reach 84%–98% compared to the energy mix in 2020. The effects on emission intensity of shifting the turbine mix towards larger sizes, reducing wind curtailment and using advanced designs to improve efficiency were further investigated. Advanced design of turbines can further decrease GHG emission intensity by 21.6%, more than the scenario of reducing curtailment (5.4%), while the emission intensity could be reduced by 2.1% under the scenario of shifting the turbine mix towards larger sizes. The results will aid future energy-mix scenario design and policy formulation. Highlights: We reviewed the LCA studies of wind energy in China. Simplified LCA models were developed to estimate the GHG emissions of China's wind energy. GHG emission intensity of China's wind industry was 19.88 g CO2 eq/kWh in 2019. Wind energy in China has an emission intensity over 98% lower than fossil fuels. Mitigation potential through deploying large and design-efficient turbines and reducing wind curtailment were quantified.